First DMAP-mediated direct conversion of Morita–Baylis–Hillman alcohols into γ-ketoallylphosphonates: Synthesis of γ-aminoallylphosphonates - Ayadi, Marwa; Elleuch, Haitham; Vrancken, Emmanuel; Rezgui, Farhat (Beilstein Journal of Organic Chemistry, 2016)
An efficient synthesis of a series of γ-ketoallylphosphonates through a direct conversion of both primary and secondary Morita–Baylis–Hillman (MBH) alcohols by trialkyl phosphites with or without DMAP, used as additive, and under solvent-free conditions, is described herein for the first time. Subsequently, a highly regioselective Luche reduction of the primary phosphonate 2a (R = H) gave the corresponding γ-hydroxyallylphosphonate 5 that further reacted with tosylamines in the presence of diiodine (15 mol %) as a catalyst, affording the corresponding SN2-type products 6a–d in 63 to 70% isolated yields. Alternatively, the alcohol 5 produced the corresponding acetate 7 which, mediated by Ce(III), was successfully converted into the corresponding γ-aminoallylphosphonates 8a–d.
Keywords: allylic substitution; γ-aminoallylphosphonate; Arbuzov reaction; γ-ketoallylphosphonate; organophosphorus chemistry